Manajemen Pelayanan Inklusif; Potert Implementasi Dan Langkah Pengukuran - Taufiq, Muhammad (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2013)
Study raised the issue of inclusive service provision of public services that should be enjoyed all walks of life, including the people who need specialized service such as the disabled (disable), the aging society, pregnant women and children. Yet the provision of an accessible Service for all citizens (inclusive) in the public service sector to date has yet to be top priority for the government. it can be seen from various public facilities are available, such as the various means of transport; public transportation terminals, traffic signs, and street beacon, or the fords and-toilet public toilet. Evenithing is not fully equipped with access for the physically disabled community and other special gala community. Efforts toward an inclusive service should be implemented in a holistic (whole) ranging from aspects of policy, management of aspects, infrastructure, and cultural aspects.